Syntheses of Some 10-Anthralin Ester Derivatives as Antipsoriatic Drugs - Gharib Naseri, N.; Ashnagar, A.; Bruce, J.M. (Asian Journal of Chemistry, 2016)
In the present study, a number of 10-alkyloxy-, 10-allyloxy-, 10-phenyloxy- and 10-benzyloxycarbonyl derivatives of anthralin were synthesized with the aim of reducing the above mentioned side effects while retaining the drug efficacy for the treatment of psoriasis.